Birth weight and nutritional status of children under five in sub-Saharan Africa. - Richard Gyan Aboagye; Bright Opoku Ahinkorah; Abdul-Aziz Seidu; James Boadu Frimpong; Anita Gracious Archer; Collins Adu; John Elvis Hagan; Hubert Amu; Sanni Yaya (PLoS ONE, 2022)
Introduction Over the past three decades, undernutrition has become a major cause of morbidity and mortality among children under five years globally. Low birth weight has been identified as a risk factor for child morbidity and mortality, especially among children under five years in sub-Saharan Africa. There is, however, a paucity of empirical literature establishing the association between low birth weight and undernutrition in sub-Saharan Africa. We examined the association between birth weight and nutritional status of children under five in sub-Saharan Africa. Methods Our analyses were performed on a weighted sample of 110,497 children under five years from 32 countries in sub-Saharan Africa. Data were obtained from the Demographic and Health Surveys conducted from 2010 to 2019. We reported the prevalence of low birth weight and nutritional status (stunting, wasting, and underweight) for all the 32 countries using percentages. We used multilevel binary logistic regression to examine the association between birth weight and nutritional status (stunting, wasting, and underweight) of the children, controlling for covariates. The results of the regression analyses were presented using adjusted odds ratios (aOR) with 95% confidence intervals. Statistical significance was set at p<0.05. Results The prevalence of low birth weight was 5.4%, with the highest (13.1%) and lowest (0.9%) reportedin South Africa and Chad, respectively. The pooled prevalence of wasting, underweight, and stunting were 8.1%, 17.0%, and 31.3%, respectively. Niger had the highest prevalence of wasting (21.5%) and underweight (37.1%), whereas Burundi had the highest prevalence of stunting (51.7%). We found that children with low birth weight were more likely to be stunted [aOR = 1.68, 95% CI = 1.58-1.78], underweight [aOR = 1.82, 95% CI = 1.70-1.94], and wasted [aOR = 1.35, 95% CI = 1.20-1.38] after controlling for covariates. Conclusion Our study has demonstrated that low birth weight is a key determinant of undernutrition among children under five in sub-Saharan Africa. Policymakers need to give special attention to improving the nutritional status of children under-five years in sub-Saharan Africa by implementing measures aimed at enhancing the weight of children. To accelerate progress towards the achievement of the Sustainable Development Goal 3.2 target of ending preventable deaths of newborns and under-five by 2030, it is imperative for countries in sub-Saharan Africa to intensify interventions aimed at improving maternal and child nutrition. Specific nutrition interventions such as dietary modification counselling should prioritized.